The Degree of Students' Involvement in the Science Textbooks of the First Three Classes of the Basic Stage in Jordan - Abdelsalam M. Adili; Kawther A. Harahshe; Hussin A. Baarah (Sultan Qaboos University, 2012)
The purpose of the present study was to find the degree of students' involvement in the science textbooks of the first three classes of the basic stage in Jordan. The sample of the study was the population itself, which was three science textbooks of the first three classes of the basic stage in Jordan. A validated and reliable instrument was developed for the purpose of the study. A descriptive statistics was used. The results of the study revealed that the degree of students' involvement in the analyzed textbooks was high in the subject matter domain, low in the figures and drawings domain, and moderate in the science activities domain. The study recommended to increase the concentration on the students' involvement in the domain of figures and drawings.